2013
DOI: 10.1089/jir.2012.0097
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism of Interleukin-22 Receptor Alpha-1 Is Associated with the Development of Childhood IgA Nephropathy

Abstract: Recent studies suggest that dysregulated innate immunity plays an important role in the pathogenesis of immunoglobulin A nephropathy (IgAN). The interleukin-20 subfamily and its receptor, interleukin-22 receptor alpha-1 (IL-22R1), were recently identified as immunomodulators in human diseases, acting as mediators of mucosal host defense. However, the potential role of IL-22R1 in the pathogenesis of IgAN has not been explored. In the current study, 194 patients with IgAN and 287 normal controls were genotyped f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…A family history of chronic nephritis, susceptibility to the common cold, preference for salty foods, frequent consumption of raw eggs, and a high intake of carbohydrates, including rice, are significantly associated with increased IgAN risk (Wakai et al, 1999). In addition, many reports have indicated that certain genetic polymorphisms are associated with susceptibility to this disease (Suh et al, 2013;Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A family history of chronic nephritis, susceptibility to the common cold, preference for salty foods, frequent consumption of raw eggs, and a high intake of carbohydrates, including rice, are significantly associated with increased IgAN risk (Wakai et al, 1999). In addition, many reports have indicated that certain genetic polymorphisms are associated with susceptibility to this disease (Suh et al, 2013;Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The titles and abstracts of all articles were reviewed and 204 were excluded; full texts and data integrity were then reviewed and another 45 articles were excluded. Finally, seven clinical case-control studies were included in this meta-analysis (Lim et al, 2002;Syrjanen et al, 2002;Chin et al, 2005;Bao et al, 2007;Wang et al, 2008;Hahn et al, 2009;Suh et al, 2013). Publication years of the eligible studies ranged from 2002 to 2013.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Previous studies have demonstrated immunogenetic factors play a fundamental role in the progression of IgAN through immune defense, metabolism, and immune surveillance (Wada et al, 2003;Berthoux et al, 2011). Recently, several clinical studies have confirmed that genetic variants of immune genes might increase the risk of IgAN (Chin et al, 2005;Suh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence indicates that gene polymorphism of some genes are associated with the susceptibility of IgAN. [3][4][5] The factor of gene polymorphism is one of the most important factors which take part in the etiology of some diseases. The evidence from meta-analysis might be powerful compared with the individual investigation.…”
Section: Introductionmentioning
confidence: 99%